Differential nutrient limitation and tree height control leaf physiology, supporting niche partitioning in tropical dipterocarp forests. (29th June 2022) - Bartholomew, David C.; Banin, Lindsay F.; Bittencourt, Paulo R. L.; Suis, Mohd Aminur Faiz; Mercado, Lina M.; Nilus, Reuben; Burslem, David F. R. P.; Rowland, Lucy
Abstract: Revealing the mechanisms of environmental niche partitioning within lowland tropical forests is important for understanding the drivers of current species distributions and potential vulnerability to environmental change. Tropical forest structure and species composition change across edaphic gradients in Borneo over short distances. However, our understanding of how edaphic conditions affect tree physiology and whether these relationships drive niche partitioning within Bornean forests remains incomplete. This study evaluated how leaf physiological function changes with nutrient availability across a fine‐scale edaphic gradient and whether these relationships vary according to tree height. Furthermore, we tested whether intraspecific leaf trait variation allows generalist species to populate a wider range of environments. We measured leaf traits of 218 trees ranging in height from 4 to 66 m from 13 dipterocarp species within four tropical forest types (alluvial, mudstone, sandstone and kerangas) occurring along an <5 km edaphic gradient in North Borneo. The traits measured included saturating photosynthesis ( A sat ), maximum photosynthetic capacity ( V cmax ), leaf dark respiration ( R leaf ), leaf mass per area (LMA), leaf thickness, minimum stomatal conductance ( g dark ) and leaf nutrient concentrations (N, P, Ca, K and Mg). Across all species, leaf traits varied consistently in response to soil nutrient availability across forest types except R leaf_mass, [Mg]leaf and [Ca]leaf . Changes in photosynthesis and respiration rates were related to different leaf nutrients across forest types, with greater nutrient‐use efficiency in more nutrient‐poor environments. Generalist species partially or fully compensated reductions in mass‐based photosynthesis through increasing LMA in more nutrient‐poor environments. Leaf traits also varied with tree height, except V cmax_mass, but only in response to height‐related modifications of leaf morphology (LMA and leaf thickness). These height–trait relationships did not vary across the edaphic gradient, except for A sat, [N]leaf, [P]leaf and [K]leaf . Our results highlight that modification of leaf physiological function and morphology act as important adaptations for Bornean dipterocarps in response to edaphic and vertical environmental gradients. Meanwhile, multiple nutrients appear to contribute to niche partitioning and could drive species distributions and high biodiversity within Bornean forest landscapes. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Abstrak: Pendedahan mekanisma pembahagian nic alam sekitar di hutan tropika tanah rendah adalah penting untuk memahami pemacu taburan dan kerentanan spesies semasa terhadap perubahan alam sekitar. Struktur hutan tropika dan komposisi spesies berubah mengikut faktor edafik dalam jarak dekat. Walau bagaimanapun, pemahaman kami tentang bagaimana keadaan edafik mempengaruhi fisiologi pokok dan sama ada ia memacu pembahagian nic dalam hutan Borneo masih tidak lengkap. Kajian ini menilai bagaimana perubahan fungsi fisiologi daun dengan ketersediaan nutrien berdasarkan faktor edafik dan sama ada ia berbeza mengikut ketinggian pokok. Malah, kami menguji sama ada ciri‐ciri variasi intraspesifik daun membolehkan spesies umum mendiami persekitaraan yang lebih luas. Kami mengukur 14 ciri‐ciri daun bagi 218 pokok yang berketinggian dari 4 hingga 66 meter, melibatkan 13 spesies dipterokap dalam empat jenis hutan tropika (aluvium, batu lumpur, batu pasir, kerangas) yang wujud di sepanjang kecerunan edafik (<5 km) di Borneo Utara. Ciri‐ciri yang diukur termasuk fotosintesis menepu ( A sat ), kapasiti maksimum fotosintesis (Vcmax ), respirasi gelap daun (Rleaf ), jisim daun per permukaan (LMA), ketebalan daun, konduksian minimum stomata ( g dark ) dan kepekatan nutrien daun (N, P, Ca, K, Mg). Ciri‐ciri daun berbeza secara konsisten terhadap ketersediaan nutrien tanah dalam semua jenis hutan kecuali R leaf_mass, [Mg]leaf dan [Ca]leaf. Perubahan kadar fotosintesis dan respirasi berhubung kait dengan perbezaan nutrient daun di semua jenis hutan dan kecekapan penggunaan nutrien adalah tinggi dalam kawasan nutrien rendah. Spesies umum mengimbangi pengurangan berkaitan jisim dan fotosintesis secara separa atau penuh dengan meningkatkan LMA dalam kawasan kawasan nutrien rendah. Ciri‐ciri daun juga berbeza berdasarkan ketinggian pokok kecuali V cmax_mass apabila ia melibatkan tindak balas perubahan morfologi daun (LMA dan ketebalan daun). Hubung kait ini tidak berbeza mengikut faktor edafik kecuali A sat, [N]leaf, [P]leaf dan [K]leaf . Dapatan kajian kami menekankan bahawa perubahan fungsi fisiologi dan morfologi daun merupakan strategi penyesuaian penting pokok dipterokap Borneo sebagai tindak balas terhadap faktor edafik serta alam sekitar. Sementara itu, pelbagai nutrien menyumbang kepada proses pembahagian nic dan mampu memacu taburan spesies serta kepelbagaian yang tinggi dalam landskap hutan Borneo. Resumen: El entendimiento de los mecanismos de partición de nicho ambiental de los bosques tropicales es importante para comprender los factores que controlan las distribuciones de especies presentes actualmente en los bosques y su posible vulnerabilidad a cambios ambientales. La estructura del bosque tropical y la composición de especies varían a través de gradientes edáficos en Borneo en distancias cortas. No obstante, se desconoce cómo las condiciones edáficas afectan la fisiología de los árboles y si estas relaciones impulsan la partición de nicho dentro en los bosques de Borneo. En este estudio se evalúa la variación fisiológica foliar con la disponibilidad de nutrientes en un gradiente edáfico de escala detallada y si estas relaciones varían según la altura de los árboles. También se evalúa si la variación intraespecífica de rasgos foliares permite que las especies generalistas habiten en un rango más amplio de entornos ambientales. Se midieron rangos foliares en 218 árboles ‐que varían en altura de 4 a 66 m‐ de 13 especies de dipterocarpáceas dentro de cuatro tipos de bosque tropical (aluial, lutita, arenisca y kerangas) que se encuentran a lo largo de un gradiente edáfico de < 5 km en el norte de Borneo. Los rangos medidos incluyen fotosíntesis en condiciones de saturación por luz (Asat), capacidad máxima para hacer fotosintesis ( V cmax ), respiración foliar en la oscuridad ( R foliar ), masa foliar expresada en unidad de área (LMA), espesor de hoja, conductancia estomática mínima ( g min ) y concentraciones foliar de nutrientes (N, P, Ca, K, Mg). En todas las especies, la majoría de los rasgos foliares investigados mostraron una variación consistente con la disponibilidad de nutrientes del suelo en todos los tipos de bosques excepto en los siguientes rasgos: R foliar_peso, Mg foliar y Ca foliar . La variación en tatas de fotosíntesis y respiración está relacionda con diferentes nutrientes foliares en todos los tipos de bosque estudiados, mostrando mayor eficiencia en el uso de nutrientes en los ambientes más infértiles. Las especies generalistas compensaron parcial o totalmente las reducciones en la fotosíntesis expresada en unidades de peso‐ mediante el aumento de LMA en los entornos más infértiles. Los rasgos foliares presentaron variaciónes relacionadas con la altura de los árboles (excepto V cmax_mass, pero sólo en respuesta a modificaciones relacionadas con la altura en la morfología de la hoja (LMA y espesor foliar). Las relaciones altura‐rasgo no variaron a lo largo del gradiente edáfico, excepto para A sat, N foliar, P foliiar y K foliar . Nuestros resultados demuestran que la variación de la fisiología y la morfología foliar son adaptaciones importantes en las especies de la familia de las dipterocarpáceas de Borneo en respuesta a gradientes ambientales verticales y edáficos. Al mismo tiempo, nuestras medidas sugieren que múltiples nutrientes contribuyen a la partición de nicho y podrían controlar la distribución de especies y la alta biodiversidad de los bosques de Borneo.